Importance of Scientific Resources Among Local Public Health Practitioners - Fields, Robert P. (Am J Public Health, 2015)
Objectives. We examined the perceived importance of scientific resources for decision-making among local health department (LHD) practitioners in the United States. Methods. We used data from LHD practitioners (n = 849). Respondents ranked important decision-making resources, methods for learning about public health research, and academic journal use. We calculated descriptive statistics and used logistic regression to measure associations of individual and LHD characteristics with importance of scientific resources. Results. Systematic reviews of scientific literature (24.7%) were most frequently ranked as important among scientific resources, followed by scientific reports (15.9%), general literature review articles (6.5%), and 1 or a few scientific studies (4.8%). Graduate-level education (adjusted odds ratios [AORs] = 1.7–3.5), larger LHD size (AORs = 2.0–3.5), and leadership support (AOR = 1.6; 95% confidence interval = 1.1, 2.3) were associated with a higher ranking of importance of scientific resources. Conclusions. Graduate training, larger LHD size, and leadership that supports a culture of evidence-based decision-making may increase the likelihood of practitioners viewing scientific resources as important. Targeting communication channels that practitioners view as important can also guide research dissemination strategies.